Russia’s War in Ukraine and Media Solidarity (Case of Georgia) - Mariam Gersamia; Ekatherine Gigauri; Salome Mamasakhlisi; Mikheil Bodokia; Mariam Nakoevi (Athens Journal of Mass Media and Communications, 2024)
This paper delves deeply into the pivotal role that solidarity journalism plays in shaping media discourse, particularly during times of wartime and crisis, with a central focus on its profound impact during the course of Russia's war on Ukraine. By conducting a thorough investigation into the multi-dimensional aspects of solidarity journalism, this study delves into the intricate strategies media outlets employ to utilize various indicators of solidarity. These strategies are deployed not only to foster collective stress resistance, but also to provide essential psychological support to audiences during periods of upheaval. The paper emphasizes the importance of media's portrayal of prosocial behaviors and positive micro-moments, which collectively contribute to the reinforcement of resilience within communities when they are facing challenging circumstances. To contextualize its findings, the paper offers a detailed analysis of the specific case of Russia's war on Ukraine. In doing so, it underscores the instrumental role that media solidarity plays in empowering the communities directly affected by such conflicts. By leveraging solidarity journalism's inherent capacity to foster unity and resilience, media outlets can significantly contribute to mitigating the often-negative effects of fear-laden narratives during times of wartime.